Neotectonic analysis, active stress field and active faults seismic hazard assessment in Western Crete - Mountrakis, D.; Kilias, A.; Pavlaki, A.; Fassoulas, C.; Thomaidou, E.; Papazachos, C.; Papaioannou, C.; Roumelioti, Z.; Benetatos, C.; Vamvakaris, D. (Bulletin of the Geological Society of Greece, 2013)
Within the framework of this study the complicated fault system of Western Crete was napped in detail and its kinematic and dynamic setting was analysed in order to distinguish 13 major active and possible active fault zones, the seismic potential of which was assessed. Moreover, kinematic data and striations were used to estimate the corresponding stress field geometry. Two stress phases were recognized: 1st the N-S extension phase (D1) in Mid-Upper Miocene to Lower Pliocene times forming E-W normal faults that bound the Neogene basins; 2nd the E-W extension phase (D2) in Late Pliocene-recent times forming N-S trending active normal faults. Smaller, mainly NE-SW trending faults, with significant strike-slip component, indicate a kinematic compatibility to the D2 phase, acting as transfer faults between larger N-S fault zones. The faults were incorporated in a detailed seismic hazard analysis together with the available seismological data, involving both probabilistic and deterministic approaches, for seismic hazard assessment of several selected sites (municipalities).